Towards struggle as lived experience: Contemplation on homiletic research for a (post-)pandemic world - W. Wessels (Acta Theologica)
This article critically reflects on the trend of current empirical homiletic research. The propensity to privilege grounded theory without thorough theological critique becomes prominent in the interpretation of digital sermons during the national COVID-19 lockdown. The main argument of this article is concerned with the relationship between practice and academia, the prominence of thematic preaching, and the lack of alternative centres of thought. Finally, as an alternative future direction for homiletic research, the article proposes the post-colonial idea of a lived experience of struggle, along with the appreciation for critical engagement with the practice of preaching from the position of the homiletic academia.